2018
DOI: 10.3390/app8122402
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Quantum-Well Number and an AlN Electron Blocking Layer on the Electroluminescence Properties of AlGaN Deep Ultraviolet Light-Emitting Diodes

Abstract: The influence of quantum-well (QW) number on electroluminescence properties was investigated and compared with that of AlN electron blocking layer (EBL) for deep ultraviolet light-emitting diodes (DUV-LEDs). By increasing the QW number, the band emission around 265 nm increased and the parasitic peak around 304 nm was suppressed. From the theoretical calculation, the electron current overflowing to the p-type layer was decreased as the QW number increased under the same injection. Correspondingly, the light ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…This information is summarized, along with the associated complex refractive index of each material, in Table 1. We note that AlN has been used as an electron blocking layer due to improved suppression of parasitic luminescence compared to Al(Ga)N:Mg 35,36 .…”
Section: Device Compositionmentioning
confidence: 99%
“…This information is summarized, along with the associated complex refractive index of each material, in Table 1. We note that AlN has been used as an electron blocking layer due to improved suppression of parasitic luminescence compared to Al(Ga)N:Mg 35,36 .…”
Section: Device Compositionmentioning
confidence: 99%
“…However, the device performance was still limited by many factors, such as the crystal quality, electrode contacts, and conductivity. In order to improve the performance of AlN based deep UVLEDs, many works have been done to improve the crystal quality [12][13][14][15][16], the p-type doping efficiency and the device structures [17][18][19][20][21][22]. It was demonstrated that the annealing process at high temperature resulted in the improvement of AlN quality [14].…”
Section: Introductionmentioning
confidence: 99%